Role of financial and non-financial information in determining individual investor investment decision: a signaling perspective. (7th May 2020) - Naveed, Muhammad; Ali, Shoaib; Iqbal, Kamran; Sohail, Muhammad Khalid
Abstract : Purpose: The purpose of this study is to examine the role of financial and nonfinancial information in determining individual investor's investment decisions by analyzing the mediating effect of corporate reputation. Design/methodology/approach: The approach of this study is deductive; therefore, the quantitative strategy is used for data collection. Primary data are collected from individual investors actively involved in stock trading at Pakistan Stock Exchange (PSX). Structural equation modeling is used to assess structural relationships. Findings: The key findings of this study posit that financial and nonfinancial information positively influence an individual investor's investment decision. This study also provides empirical evidence confirming the mediating role of corporate reputation. Categorically, the findings indicate that financial and nonfinancial information remain significant to build perceived corporate reputation and influence investor's investment decisions. Practical implications: he proposed model presents novel insight into the individual investor's investment decision in the context of Pakistan. The findings of this study remain robust for firms listed on the stock exchange and individual investors involved in stock trading. The results of this study are substantial to individual investor's and broker for making informed financial choices. Moreover, the firms listed on the PSX can use the findings to establish improved corporate reputation through reporting detailed financial and nonfinancial information. Originality/value: Studies based on subjective measures in finance are lacking. This study contributes to the existing literature of behavioral finance by analyzing variations in investor's investment decisions explained by informational factors. The proposed model testifies the mediating role of corporate reputation in guiding investor's investment decisions, which has been overlooked by past studies. Therefore, this study seeks to fill this gap in the context of the PSX.